2005
DOI: 10.1562/2004-11-29-ra-383r.1
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Behavior of 6-Methylpterin in Aqueous Solutions: Generation of Reactive Oxygen Species¶

Abstract: Pterins are a family of heterocyclic compounds present in a wide range of living systems that participate in relevant biological functions and are involved in different photobiological processes. 6-Methylpterin (MPT) was investigated for its efficiency of singlet-oxygen (1O2) production and quenching in aqueous solution. The quantum yields of 1O2 production (phi(delta)) was determined by measurements of the 1O2 luminescence in the near-infrared upon continuous excitation of the sensitizer. Values of phi(delta)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
1
17
0
5
Order By: Relevance
“…However, in the absence of O 2 , the latter occurs. Thereby, the observed H 2 O 2 is produced from O À 2 by the following reactions: When taking into account the mechanism proposed in Scheme 3 and the fact that O [23], an observation made before for other pterin derivatives [13]. 5.…”
Section: à3mentioning
confidence: 80%
See 1 more Smart Citation
“…However, in the absence of O 2 , the latter occurs. Thereby, the observed H 2 O 2 is produced from O À 2 by the following reactions: When taking into account the mechanism proposed in Scheme 3 and the fact that O [23], an observation made before for other pterin derivatives [13]. 5.…”
Section: à3mentioning
confidence: 80%
“…of 1a (Fig. 3) The generation of H 2 O 2 during the photooxidation of other pterin derivatives (biopterin, sepiapterin, FPT, 6-methylpterin, pterin) was previously reported [13] [18] [42]. The basic form of HPT (1a) also produces H 2 O 2 under UV-A irradiation [43] in the presence of O 2 .…”
mentioning
confidence: 70%
“…Recent systematic studies of the production of 1 O 2 by oxidized and reduced pterins in aqueous solution revealed that the oxidation state of the pterin derivative, the nature of the 6-substituent on the pterin moiety, as well as the pH, considerably affect the quantum yields of 1 O 2 production (Φ Δ ) [23][24][25][26]. In these studies, Φ Δ values ( Table 2) were determined by analysis of the weak 1 O 2 NIR phosphorescence at 1270 nm, produced upon excitation of the pterins with UV-A radiation, as described in, e.g., [23,26,27].…”
Section: Production Of Singlet Oxygen By Pterin Derivativesmentioning
confidence: 99%
“…OLIVEROS et al Table 2 Quantum yields of 1 O 2 production (Φ Δ ) by pterin derivatives, rate constants of 1 O 2 total quenching (k t = k r + k q ), physical quenching (k q ) and rate constants of the chemical reaction with 1 O 2 (k r ) in air-equilibrated aqueous solutions (data from refs. [23][24][25][26]28] …”
Section: Production Of Singlet Oxygen By Pterin Derivativesmentioning
confidence: 99%
See 1 more Smart Citation